Reduced FSH and LH action: implications for medically assisted reproduction. Issue 6 (1st April 2021) - Bosch, E; Alviggi, C; Lispi, M; Conforti, A; Hanyaloglu, A C; Chuderland, D; Simoni, M; Raine-Fenning, N; Crépieux, P; Kol, S; Rochira, V; D'Hooghe, T; et al.
ABSTRACT: Luteinizing hormone (LH) and follicle-stimulating hormone (FSH) play complementary roles in follicle development and ovulation via a complex interaction in the hypothalamus, anterior pituitary gland, reproductive organs, and oocytes. Impairment of the production or action of gonadotropins causes relative or absolute LH and FSH deficiency that compromises gametogenesis and gonadal steroid production, thereby reducing fertility. In women, LH and FSH deficiency is a spectrum of conditions with different functional or organic causes that are characterized by low or normal gonadotropin levels and low oestradiol levels. While the causes and effects of reduced LH and FSH production are very well known, the notion of reduced action has received less attention by researchers. Recent evidence shows that molecular characteristics, signalling as well as ageing, and some polymorphisms negatively affect gonadotropin action. These findings have important clinical implications, in particular for medically assisted reproduction in which diminished action determined by the afore-mentioned factors, combined with reduced endogenous gonadotropin production caused by GnRH analogue protocols, may lead to resistance to gonadotropins and, thus, to an unexpected hypo-response to ovarian stimulation. Indeed, the importance of LH and FSH action has been highlighted by the International Committee for Monitoring Assisted Reproduction Technologies (ICMART) in their definition of hypogonadotropic hypogonadism as gonadal failure associated with reduced gametogenesis and gonadal steroid production due to reduced gonadotropin production or action. The aim of this review is to provide an overview of determinants of reduced FSH and LH action that are associated with a reduced response to ovarian stimulation.